Dewey, Sellars, and the Given - Kalpokas, Daniel Enrique (2012)
This paper reconstructs Dewey's criticism to classic empiricism as a criticism to what Sellars calls "The Myth of the Given". Firstly, the Myth of the Given is characterized. Secondly, Dewey's experimental conception of experience and his main objections to traditional empiricism are described. Thirdly, it is showed how those objections can be understood as objections to the Myth criticized by Sellars. Finally, some differences between Sellars and Dewey are stressed. In certain way, those differences make preferable Dewey's proposal.